The Role Of Midwives And Participation Of Postpartum Mothers In Postpartum Family PlanningThe Role Of Midwives And Participation Of Postpartum Mothers In Postpartum Family Planning - Putra Apriadi Siregar; Azhari Akmal Tarigan; Nurhayati Nurhayati; Muhammad Ancha Sitorus; Evalina Franciska Hutasoit (Jurnal Kebidanan dan Kesehatan Tradisional, 2021)
Background: Postpartum birth control is one of the family planning programs that still have low coverage. Midwives have a big role in increasing postpartum family planning coverage. Postpartum mothers will often contact the midwife so that the midwife can advise the postpartum mother to use postpartum birth control. The aim of this study is to evaluate the role of midwives and postpartum mothers in the use of postpartum family planning in the Asahan regency Methods: This study used a cross-sectional design, the location study was Asahan regency, and the population was 81 postpartum mothers in Asahan Regency. The researcher used purposive sampling with the criteria of giving birth in the last one month and having more than two children. The instrument used was a questionnaire. This research will conduct cross-tabulation distribution. Results: The results of the cross-tabulation showed that 24 birth control users at the midwife's clinic gave birth at a midwife clinic, 18 people gave birth at a midwife clinic (22.2%), and 21 people had postnatal health checks (25, 9%), received advice on using postpartum family planning as many as 15 people (18.5%) and received family planning counselling after delivery as many as 14 people (17.3%). This study indicated that postpartum family planning was carried out in the midwife clinic as many as 18 people (22.2%) and in the hospital or public health centres as many as nine people (11.1%). Conclusion: Postpartum mothers who do postpartum health checks to midwives are more likely to use postpartum family planning than postpartum mothers who do not undergo postpartum health checks. Postpartum mothers who advised to use postpartum family planning from a midwife will have a greater risk of using postpartum FP than postpartum mothers who do not receive postpartum FP.